The influence of green marketing on consumer purchase interest - Prayitno, Sentot Basuki (SEAN Institute, 2024)
The introduction of Green Marketing has encouraged companies to adopt environmental issues as part of their marketing strategy. Increasingly environmentally conscious market demands have driven attention to these issues. The purpose of writing this paper is to determine the effect of green marketing on consumer purchasing interest. This research is a literature study that focuses on the topic of the influence of Green Marketing on consumer buying interests, with inclusion criteria: publications in journals, 2013-2023 year range. The data was taken through Google Scholar, MDPI, Taylor & Francis, and analyzed using the comparative method. The result of this work is that green marketing has an important role in encouraging companies to adopt environmental issues in marketing strategies to increase consumer buying interest. The effect varies depending on contextual factors such as location, industry, and market conditions. In an era where consumers' environmental awareness is getting higher, a green marketing strategy must be comprehensive, including aspects of product quality, price, distribution, promotion, and corporate social responsibility. Increased consumer knowledge about the benefits of green marketing can influence purchase intention and purchasing decisions, and companies need to educate consumers about environmentally friendly products and meet their expectations regarding price and product quality.